2016
DOI: 10.1371/journal.pone.0162805
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation into Genetics in the Conservation of Metabolic Phenotypes in Danish and Chinese Twins

Abstract: Longitudinal twin studies on long term conservation of individual metabolic phenotypes can help to explore the genetic and environmental basis in maintaining metabolic homeostasis and metabolic health. We performed a longitudinal twin study on 12 metabolic phenotypes from Danish twins followed up for 12 years and Chinese twins traced for 7 years. The study covered a relatively large sample of 502 pairs of Danish adult twins with a mean age at intake of 38 years and a total of 181 Chinese adult twin pairs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In this study, we evaluated the genetic contributions to FPG variation by twin modelling analyses and further identified the genetic variants associated with FPG levels by GWAS. We found that the heritability of FPG was 0.68, which was consistent with the previously reported range (0.22–0.71) in mainland China [ 16 , 30 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we evaluated the genetic contributions to FPG variation by twin modelling analyses and further identified the genetic variants associated with FPG levels by GWAS. We found that the heritability of FPG was 0.68, which was consistent with the previously reported range (0.22–0.71) in mainland China [ 16 , 30 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiologic studies have found that men have a higher risk of cardiovascular mortality compared to women and have a higher risk of developing CVD at earlier onset (Leutner et al, 2016). Previous twin studies on common CVD risk factors have also established that genetic and environmental factors contributing to them often differ by sex, age, and ethnicity (Li et al, 2016;Liao et al, 2017;Poveda et al, 2017;Song et al, 2015;Tanaka et al, 2015). For example, a review of twin and family studies reported that heritability estimates range from .25 to .70 for body mass index (BMI); from .25 to .60 for triglycerides (TGs); from .50 to .60 for total cholesterol (TC); from .20 to .70 for resting systolic blood pressure (SBP); and from .10 to .50 for diastolic blood pressure (DBP; Rankinen et al, 2015).…”
mentioning
confidence: 99%
“…Participants were visited by a mobile examination unit at their home, at work or at any other place at their convenience. The participants completed three different questionnaires covering health and lifestyle, sleep and work, and diet and underwent a clinical examination including ECG, blood pressure measurement, body composition, spirometry, various anthropometric measures as well as blood, saliva and urine sampling for biobanking (Li et al, 2016).…”
Section: The Middle Age Danish Twins (Midt) Studymentioning
confidence: 99%